FORMS OF CONNECTION PEDAGOGY WITH INTEGRATION SCIENCES - Gadoeva, M.M (Innovative Development in Educational Activities, 2023)
The article discusses the concept and specificity of science, as well as some features of the functioning, integration and differentiation of science in modern conditions. The results of the division of sciences are the formation, to one degree or another of new industries. Separated independent scientific disciplines.